2017
DOI: 10.1371/journal.pone.0177159
|View full text |Cite
|
Sign up to set email alerts
|

Stretch force guides finger-like pattern of bone formation in suture

Abstract: Mechanical tension is widely applied on the suture to modulate the growth of craniofacial bones. Deeply understanding the features of bone formation in expanding sutures could help us to improve the outcomes of clinical treatment and avoid some side effects. Although there are reports that have uncovered some biological characteristics, the regular pattern of sutural bone formation in response to expansion forces is still unknown. Our study was to investigate the shape, arrangement and orientation of new bone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 43 publications
2
18
0
Order By: Relevance
“…19,20 Several animal studies have shown that tensional forces progressively widen the sutures and that cartilaginous tissue is replaced by new bone formation in irregular patterns that parallel the stretching force. 21,22 In this study, the histological evaluations showed finger-like projections of new non-lamellar bone starting from the ends of the parietal bones and extending irregularly towards the center of the expanded sutures; this was similar to the findings of previous studies using expansion devices on rat sutures. 21,23 Bone remodeling occurs via sequential steps that are mediated by osteoclasts resorbing old bone and osteoblasts depositing new bone.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…19,20 Several animal studies have shown that tensional forces progressively widen the sutures and that cartilaginous tissue is replaced by new bone formation in irregular patterns that parallel the stretching force. 21,22 In this study, the histological evaluations showed finger-like projections of new non-lamellar bone starting from the ends of the parietal bones and extending irregularly towards the center of the expanded sutures; this was similar to the findings of previous studies using expansion devices on rat sutures. 21,23 Bone remodeling occurs via sequential steps that are mediated by osteoclasts resorbing old bone and osteoblasts depositing new bone.…”
Section: Discussionsupporting
confidence: 89%
“…21,22 In this study, the histological evaluations showed finger-like projections of new non-lamellar bone starting from the ends of the parietal bones and extending irregularly towards the center of the expanded sutures; this was similar to the findings of previous studies using expansion devices on rat sutures. 21,23 Bone remodeling occurs via sequential steps that are mediated by osteoclasts resorbing old bone and osteoblasts depositing new bone. Histamine has been reported to promote osteoclastogenesis by acting on the differential expression of histamine receptors on osteoblasts and osteoclasts.…”
Section: Discussionsupporting
confidence: 89%
“…Both compressive force and hypoxia may initiate osteoclastogenesis during OTM [ 28 ]. Heavy compression causes bone fracture of finger-like patterns [ 29 ]. TNF-α levels are higher on the compression side of periodontal ligament fibroblasts than on the tension side, which may influence RANKL expression during OTM [ 30 ].…”
Section: Effects Of Mechanical Forces On Bone Metabolismmentioning
confidence: 99%
“…Palatal expansion has been widely used for the transverse discrepancy or maxillae hypoplasia, which is the main approach to stimulate bone regeneration around the suture area during orthodontics treatment 1‐3 . Palatal expansion is based on mechanical force‐induced bone remodeling, 4,5 but its underlying biological mechanisms remains largely unknown. It has been reported that osteoclasts played a crucial role during orthodontic tooth movement (OTM) and palatal expansion process 6,7 .…”
Section: Introductionmentioning
confidence: 99%